Cultivation of Acidophilic Algae Galdieria sulphuraria and Pseudochlorella sp. YKT1 in Media Derived from Acidic Hot Springs - Hirooka, Shunsuke; Miyagishima, Shin-ya (Frontiers in Microbiology, 2016)
Microalgae possess a high potential for producing pigments, antioxidants, and lipophilic compounds for industrial applications. However, the cultivation of microalgae comes at a high cost. To reduce the cost, changes from a closed bioreactor to open pond system and from a synthetic medium to environmental or wastewater-based medium are being sought. However, the use of open pond systems is currently limited because of contamination by undesirable organisms. To overcome this issue, one strategy is to combine acidophilic algae and acidic drainage in which other organisms are unable to thrive. Here, we tested waters from sulfuric acidic hot springs (Tamagawa, pH 1.15 and Tsukahara, pH 1.14) in Japan for the cultivation of the red alga Galdieria sulphuraria 074G and the green alga Pseudochlorella sp. YKT1. Both of these spring waters are rich in phosphate (0.043 and 0.145 mM, respectively) compared to other environmental freshwater sources. Neither alga grew in the spring water but they grew very well when the waters were supplemented with an inorganic nitrogen source. The algal yields were ~2.73 g dry weight/L for G. sulphuraria and ~2.49 g dry weight/L for P. sp. YKT1, which were comparable to those in an autotrophic synthetic medium. P. sp. YKT1 grew in the spring waters supplemented either of NH4+, NO3- or urea, while G. sulphuraria grew only when NH4+ was supplemented. For P. sp. YKT1, the spring water was adjusted to pH 2.0, while for G. sulphuraria, no pH adjustment was required. In both cases, no additional pH-buffering compound was required. The phycocyanin of the thermophilic G. sulphuraria is known to be more thermostable than that from the Spirulina platensis currently used in phycocyanin production for commercial use. The phycocyanin content in G. sulphuraria in the Tsukahara water supplemented with NH4+ was 107.42±1.81 μg/mg dry weight, which is comparable to the level in S. platensis (148.3 μg/mg dry weight). P. sp. YKT1 cells in the Tamagawa water supplemented with a nitrogen source formed a large amount of lipid droplets while maintaining cellular growth. These results indicate the potential of sulfuric hot spring waters for large-scale algal cultivation at a low cost.